The Impact of Short-term Financial Leverage on Financial Performance of Syrian Private Traditional Banks -Econometric Study using Threshold Model - (Journal of Hama University, 2022)
This study aims to identify the impact of short-term financial leverage on the financial performance of traditional private banks operating in Syria in the period between 2011-2019. The short-term financial leverage was expressed as the ratio of short-term liabilities and short-term deposits to total assets, and the financial performance by the adjusted RoA ratio, and the following control variables were used: the efficiency of operations, the size of credit facilities, the inflation rate, and the effective real exchange rate. Using annual data, Threshold methodology was applied to Panel data. The results showed that the impact of financial leverage on financial performance is a non-linear effect, which appears through the regimes of the relationship as follows: In the first regime when the financial leverage is less than 26.72% (the first threshold), the effect is significantly positive, and in the second regime when the financial leverage ratio is greater than 26.72% and less than 42.81% (between the two thresholds), the effect is significantly positive and greater than the effect in the first regime. As for the third regime, where the financial leverage ratio is less than 42.81% (the second threshold), the effect becomes significantly negative
Keywords: Financial Leverage, Financial Performance, Non-Linear Relationship, Threshold Methodology, Financial Structure.